AZAS LEGALITAS DALAM HUKUM PIDANA ISLAM (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2017)
This study is started by a research about the importance of legality principle which is as a prior principle in Islamic civil law. The legality principle is stated by Paul Johan Anselm von Feurbach. At least the legality principle is locked in postulate “mullum dellictum nulla poena sine praevia lege poenali” that there is no criminal offense before the former criminal constitution. And actually Islamic law has adopted this principle formerly. It is proven by the legality principle printed implisitly in Al-qur’an or some hadits.